2010
DOI: 10.1007/s11136-010-9678-5
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary findings of an investigation into the relationship between national culture and EQ-5D value sets

Abstract: The correlation patterns observed are generally consistent with a priori expectations based on the nature of the dimensions of culture and the EQ-5D model. This analysis demonstrates the potential of national culture in providing insight into the drivers of the relative values of EQ-5D dimensions for different countries and in informing decisions about which EQ-5D value sets to use in situations where one does not exist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
48
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 11 publications
(9 reference statements)
0
48
4
Order By: Relevance
“…However, in practice, the country-specific tariff is not always available, and in such scenarios, tariffs derived from other countries can be adopted. Literature indicates that different cultures could influence the derived utility scores 31,32. Previous studies regarding the EQ-5D-3L instrument and its tariffs showed that it would be better to choose tariffs with similar cultural backgrounds 26,27,33.…”
Section: Discussionmentioning
confidence: 99%
“…However, in practice, the country-specific tariff is not always available, and in such scenarios, tariffs derived from other countries can be adopted. Literature indicates that different cultures could influence the derived utility scores 31,32. Previous studies regarding the EQ-5D-3L instrument and its tariffs showed that it would be better to choose tariffs with similar cultural backgrounds 26,27,33.…”
Section: Discussionmentioning
confidence: 99%
“…Details of patients characteristics and methods of data collection appear in the sources cited. Some of the patients in the original stroke study had been recruited outside the UK but their records were omitted from this analysis, as there are grounds for believing that EQ-5D responses vary geographically [21]. The other studies had been conducted with UK subjects only.…”
Section: Methodsmentioning
confidence: 99%
“…Linear regression analysis showed that gross domestic product explained 67% of the EQ visual analogue scale (p = 0.02) when outliers were excluded and 29% when the outliers were included; per-capita health expenditure explained 26% of the mean visual analogue scale (p = 0.03). Finally, in a preliminary study of the relationships between national culture and EQ-5D value sets, power distance (that is, a society in which people expect and desire inequalities among themselves) and individualism were found to have moderate and strong correlations with pain and discomfort, and anxiety and depression 22 .…”
Section: Introductionmentioning
confidence: 96%
“…Differences in age, sex, standard of living, and preferences by health state in the general population of various countries can potentially contribute to cultural differences in a model 22,23 . For example, a French valuation study found that French respondents weighted problems in the mobility, self-care, and usual activity parameters more heavily than did U.K. respondents 24 .…”
Section: Introductionmentioning
confidence: 99%